Global Mobile Satellite Communications Applications For Maritime, Land and Aeronautical Applications Volume 2 - Ilcev, Stojce Dimov (Springer International Publishing, 2018)
This book discusses global mobile satellite communications (GMSC) for maritime, land (road and rail), and aeronautical applications. It covers how these enable connections between moving objects such as ships, road and rail vehicles and aircrafts on one hand, and ground telecommunications subscribers through the medium of communications satellites, ground earth stations, Terrestrial Telecommunication Networks (TTN), Internet Service Providers (ISP) and other wireless and landline telecommunications providers. The new edition covers new developments and initiatives that have resulted in land and aeronautical applications and the introduction of new satellite constellations in non-geostationary orbits and projects of new hybrid satellite constellations. The book presents current GMSC trends, mobile system concepts and network architecture using a simple mode of style with understandable technical information, characteristics, graphics, illustrations and mathematics equations. It represents telecommunications technique and technology, which can be useful for all technical staff on vessels at sea and rivers, on all types of land vehicles, on planes, on off shore constructions and for everyone possessing satellite communications handset phones. The first edition of Global Mobile Satellite Communications (Springer, 2005) was split into two books for the second edition - one on applications and one on theory. This book presents global mobile satellite communications applications.